Star Gazing - Strategien der medialen Inszenierung bei Alfred Hitchcock und Gilbert & George - Seligmann, Nadine (transcript-Verlag, 2018)
As much as the powerful appearance of film-maker Alfred Hitchcock still fascinates today, artists Gilbert & George have created a unique brand identity over several decades. Assuming that star personas are constituted by performative acts and rely on mechanisms of repetition, the focus lies on exploring these complex star phenomena through their individual performances and appearances, as they generate a coherent image across various media. Great attention is also attached to paratexts, such as trailers, print advertising, and photographs